(untitled) (Evidence-Based Pharmacotherapy in Clinical Practice, 2025)
Author Miss Pravallika V PharmD Intern, Department of Pharmacy Practice, Koringa College of Pharmacy, Korangi, Andhra Pradesh, India Abstract Pain management protocols incorporate systematic assessment tools and multimodal therapeutic approaches based on pain classification and severity. Acute pain interventions utilize stepwise analgesic selection with regular reassessment of pain control and functional improvement. Chronic pain management employs multiple drug classes including opioids, adjuvant analgesics, and topical agents with emphasis on functional improvement and quality of life measures. Cancer pain protocols incorporate regular assessment tools, breakthrough pain management, and route of administration optimization based on disease progression. Palliative care approaches emphasize symptom control and quality of life optimization through systematic assessment and intervention protocols. Non-pharmacological approaches integrate physical modalities, psychological interventions, and complementary therapies with conventional analgesic strategies. Treatment selection considers pain mechanisms, comorbid conditions, and risk factors for adverse effects Keywords: Pain assessment, Analgesic selection, Cancer pain, Palliative care, Multimodal therapy VIEW PDF